Intent to quit, quit attempts, and perceived health risk reduction among African American, Latino, and White nondaily and daily smokers in the United States. Issue 8 (17th November 2019) - Scheuermann, Taneisha S.; Nollen, Nicole L.; Luo, Xianghua; Cox, Lisa Sanderson; Ahluwalia, Jasjit S.
ABSTRACT: Objective: Ethnic and racial differences in smoking patterns and behaviors have been well documented and most African American and Latino smokers are nondaily or light smokers. However, differences within smoking levels are understudied. Our primary aim was to determine whether there are racial and ethnic differences among African American, Latino, and White nondaily, light daily, and moderate to heavy daily smokers on (1) perceived health risk reduction, (2) intentions to quit, and (3) past year quit attempts. Design: Smokers were recruited through an online research panel for a cross-sectional survey ( n  = 2376). Sampling quotas were used to obtain equal numbers of African American, Latino, and White nondaily and daily smokers. Results: African American (59.6%) and Latino (54%) nondaily smokers were more likely than White nondaily smokers (45%) to currently limit their cigarettes per day (cpd) as a perceived health risk reduction strategy ( p  < 0.05). African American nondaily smokers were more likely than Latino and White nondaily smokers ( p  < 0.05) to limit their smoking in the past year as a perceived health risk reduction strategy (range: 0 'never' to 5 'always'; Means = 3.2, 2.9, 3.0, standard deviations [SD] = 1.1, 1.1, 1.2, respectively). African American nondaily smokers (15%) were more likely than either Latinos (7.8%) or Whites (8.5%) to intend to quit in the next 30 days ( p  < 0.01). African American (61.6%) and Latino (60.3%) nondaily smokers were more likely than Whites (49%) to have made a quit attempt in the past year ( p  < 0.01). Fewer racial and ethnic differences were found among daily smokers. Conclusions: Racial and ethnic group differences were more pronounced among nondaily smokers compared to light daily smoker and moderate to heavy daily smokers. Smoking level is an important consideration in understanding racial and ethnic variation in perceived health risk reduction and cessation-related behaviors.